“DANA” Usage : The effect of perceived ease of use & perceived security: “DANA” Usage : Pengaruh perceived ease of use & perceived security - Anisa Yuniar Safira; Astri Yuza Sari (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
The use of E-wallets has grown rapidly, but the challenge of maintaining users for sustainability amid fierce competition and attention to the security of personal data is an issue that needs to be analyzed. This study aims to determine the effect of Perceived Ease Of Use and Perceived Security on e-Wallet “Dana” Usage: Continuous Intention e Wallet “Dana” as a Mediating Variable. This research sampling technique with certain criteria. The research participants totaled 208 respondents who were selected as samples. Data were collected through online distribution of questionnaires and then analyzed using SmartPLS 4.0 software. The results of this study reveal that (1) perceived ease of use has no significant effect on continuous intention, (2) perceived security has a positive and significant effect on continuous intention, (3) perceived ease of use has a direct effect on e-wallet usage, (4) perceived security has no direct effect on e-wallet usage, (5) Continuous Intention affects e-wallet usage, (6) Continuous Intention does not mediate the relationship between perceived ease of use and e-wallet usage. (7) Continuous Intention mediates the relationship between perceived security and e-wallet usage.